D DanteNZ New member Joined Mar 12, 2011 Messages 5 Mar 31, 2011 #1 Hey just wondering how I would go about this equation. Solve 4x + (1, -1, 3) = (1, 3, -5) for x.

D DanteNZ New member Joined Mar 12, 2011 Messages 5 Mar 31, 2011 #2 I have tried doing this. 4x = (1, -1, 3) - (1, 3, -5) x = (1/4, -1/4, 3/4) - (1/4, 3/4, -5/4) But that can't be right surely?

I have tried doing this. 4x = (1, -1, 3) - (1, 3, -5) x = (1/4, -1/4, 3/4) - (1/4, 3/4, -5/4) But that can't be right surely?

mmm4444bot Super Moderator Staff member Joined Oct 6, 2005 Messages 10,251 Apr 1, 2011 #3 DanteNZ said: 4x = (1, -1, 3) - (1, 3, -5) The vectors are transposed in your subtraction (i.e., you subtracted the wrong vector). x = (1/4, -1/4, 3/4) - (1/4, 3/4, -5/4) Do the subtraction first, then divide both sides by 4. Click to expand...

DanteNZ said: 4x = (1, -1, 3) - (1, 3, -5) The vectors are transposed in your subtraction (i.e., you subtracted the wrong vector). x = (1/4, -1/4, 3/4) - (1/4, 3/4, -5/4) Do the subtraction first, then divide both sides by 4. Click to expand...